2014
DOI: 10.1095/biolreprod.114.118869
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic Peptide Precursor C Delays Meiotic Resumption and Sustains Gap Junction-Mediated Communication in Bovine Cumulus-Enclosed Oocytes1

Abstract: Oocyte in vitro maturation (IVM) has become a valuable technological tool for animal breeding and cloning and the treatment of human infertility because it does not require the administration of exogenous gonadotropin to obtain fertilizable oocytes. However, embryo development after IVM is lower compared to in vivo maturation, most likely because oocytes collected for IVM are heterogeneous with respect to their developmental competencies. Attempts to improve IVM outcome have relied upon either prematuration cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
112
2
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(141 citation statements)
references
References 45 publications
13
112
2
14
Order By: Relevance
“…In contrast to our results, Franciosi et al (2014) demonstrated that 100 nM of NPPC delayed oocyte meiosis resumption after 6 or 8 h of culture, maintaining communication via gap junctions in bovine COCs. However, as observed by Bilodeau-Goeseels (2007) for NPPA in bovine, we similarly demonstrated that none of the NPs (NPPA, NPPB and NPPC), individually or combined, inhibit the rate of meiosis resumption in bovine oocytes (supplementary data).…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our results, Franciosi et al (2014) demonstrated that 100 nM of NPPC delayed oocyte meiosis resumption after 6 or 8 h of culture, maintaining communication via gap junctions in bovine COCs. However, as observed by Bilodeau-Goeseels (2007) for NPPA in bovine, we similarly demonstrated that none of the NPs (NPPA, NPPB and NPPC), individually or combined, inhibit the rate of meiosis resumption in bovine oocytes (supplementary data).…”
Section: Discussioncontrasting
confidence: 99%
“…NPR2 stimulation by CNP increased cGMP intracellular concentrations in both CCs and the oocyte and maintained meiotic arrest (Zhang et al 2010). CNP has since been identified as an oocyte-meiosis-inhibiting peptide in a range of species such as mice (Zhang et al 2010), swine (Santiquet et al 2014), cattle (Franciosi et al 2014) and rats (Zhang et al 2015). The physical characteristics and mode of action of CNP suggest it is likely to be the oocyte maturation inhibitor (OMI) found in follicular fluid, as described several decades ago (Tsafriri et al 1976).…”
Section: Contribution Of Natriuretic Peptides To Meiotic Arrestmentioning
confidence: 90%
“…Application of CNP (10–100 nM) to cumulus-oocyte complexes from mice (66, 74), pigs (75, 76), cows (77), and domestic cats (78) inhibits meiotic resumption. CNP does not inhibit meiotic resumption in isolated oocytes (66, 75, 76) because oocytes do not express NPR2 (66).…”
Section: Meiotic Prophase Arrestmentioning
confidence: 99%